2021
DOI: 10.24926/iip.v12i3.2310
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Team-Based Video Simulation to Complement a Lecture in Motivational Interviewing to Develop Students’ Initial Attitudes and Skills

Abstract: Background: Motivational interviewing (MI) is increasingly recognized for its patient-centered approach to clinician-patient communication and often effective in evoking appropriate changes in patient behavior.  Doctor of Pharmacy (PharmD) programs are increasingly incorporating MI education; however, doing so represents a challenge regarding availability of both time and labor capital. Case Description: This study reports on the use of a 90-minute software-based simulation and tutorial coupled with a 90-minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Multiple studies demonstrated improved pharmacy student communication skills in terms of confidence, satisfaction, and skill development when using SPs 5–9 . There is some literature demonstrating SPs have been utilized in teaching MI to pharmacy students 10–12 . Stafford et al report utilizing SPs to evaluate student case scores which improved from 81.9% to 86.9% in a second professional year reinforcement course after an introductory MI module was added to the first professional year 10 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies demonstrated improved pharmacy student communication skills in terms of confidence, satisfaction, and skill development when using SPs 5–9 . There is some literature demonstrating SPs have been utilized in teaching MI to pharmacy students 10–12 . Stafford et al report utilizing SPs to evaluate student case scores which improved from 81.9% to 86.9% in a second professional year reinforcement course after an introductory MI module was added to the first professional year 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A team‐based approach utilizing video simulation with a lecture in which groups interviewed SPs was evaluated by Malewski et al Instruction involved lectures, case simulations, provided by the National Healthcareer Association in which students working with set patient case video scenarios were asked questions that could be selected from several different potential responses, and group interviews of SPs. While students gained foundational skills in MI competency, work with SPs demonstrated they fell short on ability to implement them 11 . Galal et al looked at the impact of MI training on students' social/emotional development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations